Analisis Penerapan Problem Based Learning dalam Kemampuan Berpikir Kritis Siswa pada Pelajaran Matematika - Aulia Masruro, Anisyah; Yatmo Dwi Harjo, Fredi; Nur Arifah, Siti; Surur, Miftahus (Education Journal : Journal Educational Research and Development, 2024)
Problem-based learning is a student-centred problem-based learning method. This learning Model is one of the learning models that is very closely related and has significant value in improving critical thinking skills in students. This study aims to describe the effect of the application of Problem-Based Learning on students ' critical thinking skills in Mathematics. The method used in this study is a literature review. The results of the analysis of this study indicate that Problem-Based Learning is one of the learning models that can improve students ' critical thinking skills significantly.